Mengenal Merek : Pengertian, Kriteria, dan Macam-Macam Merek Produk dan Jasa Dalam Bidang Rias - nathania, novita (Journal of Beauty and Cosmetology (JBC), 2022)
The field of beauty and makeup at this time has become a very important thing for all women. Which at the moment there are various brands. Starting from the well-known ones to new brands that have just emerged. This is certainly a fun thing for women. Therefore, in this journal, the author wants to explore more deeply about brands that contain brand understanding, brand criteria and various kinds of brands of natural products and services in the field of makeup. The method carried out in this study is descriptive analysis where the observation is carried out with reference to previous studies (literature review) the results of writing this journal that there are a large number of brands of products and services in the field of makeup. Which of course we must be careful in choosing the brand so as not to harm ourselves.Keywords: Beauty, Brand, Criteria